Sexual risk behaviors of African American men who have sex with men: implication of situational factors and partner dynamics - Saleh, L (2013)
HIV infection disproportionately burdens Black men who have sex with men (MSM) living in the United States. Qualitative research is able to richly contextualize the HIV risk factors of Black MSM, but to date limited qualitative evidence exists. This study set out to: (a) examine how participants perceived their childhood experiences to impact their adult sexual behaviors; (b) describe the situational context and the main perceived drivers of high and low risk behaviors, and contextualize these behaviors according to life circumstances at the time; and (c) explore participants' perceived sources of social support, and understand how the quality of this social support may influence participants' psychological well-being and HIV risk behaviors. Semi-structured in-depth interviews were conducted with 34 Black MSM in Providence, Rhode Island, USA. Thematic analysis sought to understand the factors contributing to an episode of protected sex and unprotected sex occurring within the previous 12 months. Narratives suggest that sexual risk behaviors are not isolated events, but instead the result of a lifetime of experiences that may influence attitudes and beliefs toward sexual safety, mental and emotional health, and self-efficacy for condom use. Participants perceived that: (a) interpersonal, internal/psychological, and episodic factors influenced their high risk and low risk sexual behaviors; (b) childhood socioeconomic status, family characteristics, and experiences of abuse were among the most important childhood factors implicated in their adult sexual behaviors; and (c) limited social support led to feelings of loneliness, isolation, and alienation, which may have led participants to seek intimacy through high-risk sexual episodes. This thesis suggests that complex interrelated factors underlie the sexual risk behaviors of Black MSM. Future HIV prevention efforts must extend beyond safer-sex approaches and address the social-ecological determinants of sexual behaviors. Further qualitative examination can deepen understanding of Black MSM’s sexual behaviors, provide meaningful insight into the factors driving unprotected sexual behaviors, and uncover novel points for intervention.